Does an online psychological intervention improve self-efficacy and disability in people also receiving Multimodal Manual Therapy for chronic low back pain compared to Multimodal Manual Therapy alone? Design of a randomized controlled trial. Issue 1 (December 2015) - Petrozzi, M.; Leaver, Andrew; Jones, Mairwen; Ferreira, Paulo; Rubinstein, Sidney; Mackey, Martin
Abstract Background Various interventions are available for the treatment of chronic low back pain (LBP), including Manual Therapy and Cognitive Behavioural Therapy (CBT). The purpose of this study is to evaluate whether the addition of an internet-based CBT program leads to better outcomes in patients who are treated with multimodal manual therapy for chronic LBP. Methods/Design A randomized controlled trial comparing a combined intervention, consisting of internet-based CBT utilising MoodGYM plus multimodal manual therapy, to multimodal manual therapy alone for patients with chronic LBP. Multimodal manual therapy will be delivered by experienced chiropractors and physiotherapists. Treatment sessions will consist of a combination of joint and soft tissue mobilisation; spinal manipulation as well as muscle and fascia massage; education and reassurance; and rehabilitative exercise prescription. In total, 108 adult participants will be recruited from multiple chiropractic and physiotherapy private practices in Australia. Participants older than 18 years of age and diagnosed with chronic non-specific LBP will be included in the trial, where chronic LBP is defined as continuous or fluctuating pain for a minimum of three months. The Keele STarT Back screening tool will be used to screen for potential participants who are in the medium risk category. The primary outcomes are self efficacy and disability measured by the Patient Self-Efficacy Questionnaire (PSEQ) and Roland Morris Disability Questionnaire (RMDQ) respectively. Secondary outcome measures will assess pain, catastrophising, depression, anxiety, stress and work ability. Participants will be randomly allocated into one of two groups. Both groups will receive an upper limit of 12 multimodal manual therapy sessions over a period of 8 weeks. The intervention group will also receive five weeks of MoodGYM covering five modules in total. Assessment will be conducted at pre-treatment, post-treatment 8- and follow-up at 26- and 52 weeks. In addition, a verbal pain measure will be completed by the treating practitioner at time of treatments on an 11-point VAS. The primary data analysis will be by intention to treat using a linear mixed model for each outcome. Discussion This paper outlines the design of a randomised controlled trial that investigates the potential benefits of adding a widely available and inexpensive internet-based psychological intervention to standard multimodal manual therapy for the management of chronic low back pain. Trial registration ACTRN12615000269538